Line intensities for the ν6 and 2ν3 bands of methyl iodide (12CH3I). (January 2019) - Kwabia-Tchana, F.; Attafi, Y.; Manceron, L.; Doizi, D.; Vander Auwera, J.; Perrin, A.
Abstract: The goal of this study is to measure for the first time absolute line intensities for the ν6 band of methyl iodide (CH3 I) centered at 892.918 cm –1 . High-resolution Fourier transform spectra were recorded at various pressures for the whole 500–1450 cm –1 spectral range. Using these spectra, a large set of CH3 I individual line intensities was measured for the ν6 band. These experimental intensities were least squares fitted to derive the expansion of the ν6 transition moment operator. The theoretical model used to describe the line positions and intensities accounts for the hyperfine structure in the 6 1 and ground states and for the vibration-rotation resonances that couple the 6 1 energy levels with those of the 3 2 and 2 1 vibrational states [Perrin et al., J. Mol. Spectrosc. 324 (2016) 28–35]. As the 2ν3 band is extremely weak, its associated transition moment operator was estimated from band strength available in the literature. A comprehensive list of line positions and intensities was generated for the ν6 and 2ν3 bands of CH3 I at 11 µm, which should be useful for the possible detection of this species by the future IASI-NG satellite instrument (Infrared Atmospheric Sounding Interferometer New Generation), now under preparation (https://iasi-ng.cnes.fr/en/IASI-NG/index.htm ). Graphical abstract: Image, graphical abstract